A Case Study of Systemic Lupus Erythematosus Patient Presenting with Lupus Panniculitis of the Lower Extremities as an Initial Manifestation: A Rare Case - Hamid M. Mustafa (Journal of King Abdulaziz University: Medical Sciences, 2023)
Lupus erythematosus panniculitis is a quite rare entity disease, and to our knowledge occurs in the lower extremity as an initial manifestation of Systemic lupus erythematosus which is very rarely reported. This report presents a case of a 36-year-old female who presented with recurrent subcutaneous nodules on her lower extremities. Further history and physical examination revealed hands and knee joints arthritis with recurrent painless oral ulceration. The blood work performed on the patient revealed positive antinuclear antibody and anti?double strand DNA; hence, the diagnosis of Systemic lupus erythematosus was determined. Skin biopsy was performed and showed lobular panniculitis with heavy infiltration of lymphocyte and plasma cells, and the diagnosis of lupus panniculitis was confirmed. Treatment was started with low doses of systemic steroids and hydroxychloroquine, which resulted in complete clinical remission.